Rare and protected species of flora of wetlands places of the Kharkiv region (Ukraine) - Rokytyansky, A.; Gamulya, Yu. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The article presents the results of the research of rare and protected species of wetlands places flora of the Kharkiv region. According to the field studies results, literary sources analysis and materials of the CWU and KW herbarium, it has been established that at least 225 species of vascular plants are present in the flora of wetlands places. The annotated list of rare and protected species of flora of wetlands places in the region has been made. It contains 41 species. For each species, the status of protection is defined. 32 species are identified as insufficiently studied and requiring detailed research and estimation of their sozological significance, in order to determine the need for their protection at the regional level. In total, 15 species from the identified are listed in the Red Data Book of Ukraine: Lycopodiella inudata (L.) (Holub); Drosera anglica Huds.; Cirsium heterophyllum (L.) Hill; Caldesia parnassifolia (L). Parl.; Fritillaria meleagroides Patrin ex Schult. et Schul. fil.; Fritillaria meleagris L.; Anacamptis coriophora (L.) R.M.Bateman; Anacamptis palustris (Jacq.) R.M.Bateman, Pridgeon & M.W.Chase; Dactylorchiza fuchsii (Druce) Soo; Dactylorchiza incarnata (L.) Soo; Dactylorchiza majalis (Reichenb.) P.F.Hunt et Summer.; Epipactis palustris (L.) Crantz; Hammarbya paludosa (L.) O.Kuntze); Liparis loeselii (L.) Rich.; Scheuchzeria palustris L. 26 species are from the List of plant species which need the special protection in the territory of the Kharkiv region. One species is endemic (Rorippa brachycarpa (C.A.Mey) Hayek), one species is the tertiary relic (Caldesia parnassifolia (L.) Parl.). Five species of wetlands places flora (Anacamptis coriophora (L.) R.M.Bateman; Anacamptis palustris (Jacq.) R.M.Bateman, Pridgeon & M.W.Chase; Dactylorchiza fuchsii (Druce) Soo; Dactylorchiza majalis (Reichenb.) P.F.Hunt et Summer.; Liparis loeselii (L.) Rich.) are listed in the CITES; three species (Dactylorchiza incarnata (L.) Soo; Epipactis palustris (L.) Crantz.; Hammarbya paludosa (L.) O.Kuntze) are listed in the CITES Appendix ІІ. Two species (Caldesia parnassifolia (L.) Parl., Liparis loeselii (L.) Rich.) are listed in the Annex I of the Berne Convention. Communities of Glycerieta arundinaceae are listed in the Green Book of Ukraine. Six associations and formations are rare plant communities of the Green list of the Kharkiv region. It has been established that in total under the protection are 41 species of vascular plants of wetlands places flora that is 18.2% of the total number of species attributed to this ecological group, or 3.2% of the total Kharkiv region flora.